If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2) + 2y = 16 Multiply 8 * 2 16 + 2y = 16 Add '-16' to each side of the equation. 16 + -16 + 2y = 16 + -16 Combine like terms: 16 + -16 = 0 0 + 2y = 16 + -16 2y = 16 + -16 Combine like terms: 16 + -16 = 0 2y = 0 Solving 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 0 Simplifying y = 0
| 4+3m=16 | | -5d+10=-15 | | 1-7t=78 | | 10+7k=-11 | | -5d+8=-7 | | -3k+5=23 | | 2*-5-5*0=10 | | 4d-2=46 | | -9+4w=35 | | 3w+2=26 | | -1-3b=5 | | 6w-6=60 | | 2w+4=-12 | | 10-5m=5 | | -7w+10=-4 | | 5+2m=-9 | | 2b+7=13 | | 6t+1=-71 | | 8-4m=48 | | 5+5m=35 | | 6a+8=74 | | -4+7w=-60 | | -2-5x=-62 | | (x-1)(x+2)=40 | | x^2+2x-1=4x+3 | | -3d-1=-1 | | 3-6m=-69 | | -10+3n=14 | | 7n-8=-57 | | 10+4w=-26 | | (4x^2-8x+16)-49=0 | | 7m+2=-33 |